Extraction of thermal characteristics of surrounding geological layers of a geothermal heat exchanger by 3D numerical simulations. (25th April 2016) - Aranzabal, N.; Martos, J.; Montero, Á.; Monreal, L.; Soret, J.; Torres, J.; García-Olcina, R.
Highlights: An innovative analysis procedure, complementing the standard TRT analysis. A novel temperature profile is presented as an additional measurement during the TRT. Estimate thermal conductivity profile of geothermal layers crossed by perforation. Implemented by fitting 3D FEM simulation results with experimental data. Allowed the detection of a highly conductive layer in an experimental BHE installation. Abstract: Ground thermal conductivity and borehole thermal resistance are key parameters for the design of closed Ground-Source Heat Pump (GSHP) systems. The standard method to determine these parameters is the Thermal Response Test (TRT). This test analyses the ground thermal response to a constant heat power injection or extraction by measuring inlet and outlet temperatures of the fluid at the top of the borehole heat exchanger. These data are commonly evaluated by models considering the ground being homogeneous and isotropic. This approach estimates an effective ground thermal conductivity representing an average of the thermal conductivity of the different layers crossed by perforation. In order to obtain a thermal conductivity profile of the ground as a function of depth, two additional inputs are needed; first, a measurement of the borehole temperature profile and, second, an analysis procedure taking into account ground is not homogeneous. This work presents an analysis procedure, complementing the standard TRT analysis, estimating the thermal conductivity profile from a temperature profile along the borehole during the test. The analysis procedure is implemented by a 3D Finite Element Model (FEM) in which depth depending thermal conductivity of the subsoil is estimated by fitting simulation results with experimental data. The methodology is evaluated by the recorded temperature profiles throughout a TRT in a BHE (Borehole Heat Exchanger) monitored facility, which allowed the detection of a highly conductive layer at 25 meters depth.